2021
DOI: 10.1186/s12889-021-11733-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of price on cigarette consumption, distribution, and sale in Tehran: a qualitative study

Abstract: Background Appropriate increases in tobacco taxes and prices are an essential component of comprehensive tobacco control strategies. This study investigates factors related to the use, sale, and distribution of cigarettes in Iran, focusing on the relationship between cigarette price and its consumption. Methods This interview-based qualitative study was conducted among 20 participants, including cigarette smokers, retail shop owners, large-scale di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This difficulty stems from the inadequacy of current policy execution. Evidence suggests the economic recession in Iran in recent years has led to a decreased cigarette consumption due to affordability concerns, resulting in a towards purchasing single-stick cigarettes instead of whole boxes 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This difficulty stems from the inadequacy of current policy execution. Evidence suggests the economic recession in Iran in recent years has led to a decreased cigarette consumption due to affordability concerns, resulting in a towards purchasing single-stick cigarettes instead of whole boxes 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ghelichkhani et al studied individuals aged 7 to 70 years, which may have diluted the impact of SES status on WTS. Relatedly, the preparation of WTS or gathering in groups of friends at hookah café requires time and may cost more for people from a low-income neighborhood, contrary to cigarettes that are more easily accessible and cheaper for this low SES group [ 47 ]. In contrast to the findings of the present study, a study of Iranian adults in 2010 suggested that income had no significant effect on hookah use [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purchase pattern of Iranian smokers has changed from the whole box of cigarettes to the single stick cigarette. In addition, smokers have generally swapped to less expensive cigarettes (29). Dealing with the burden attributable to tobacco use, public health authorities encounter substantial obstacles such as an increased number of smokers due to population growth, pressure from the tobacco industry, and competing for health and political priorities (1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the revenue from tobacco taxation needs to be redistributed to tobacco control programs, health care services, and social support services (30). Unless strict regulations are in place to control cigarette smuggling, any increase in cigarette price could be compensated by ooding smuggled cigarettes into the market (29). This calls for substantially reducing smoking rates in the country via adopting, implementing, and enforcing comprehensive packages of evidence-based tobacco control policies.…”
Section: Discussionmentioning
confidence: 99%